BRANDING STRATEGY EXPLORATION IN BUILDING BRAND AWARENESS IN COFFEE SHOP MSMEs IN KENDARI CITY - Muh. Husriadi; Maulidia Berlianti; Iwan Patta (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
The development of coffee MSME-based shops in Kendari City show that competition is no longer only determined by product quality, but also by the ability to build a brand. awareness through consistent branding strategies. This situation drives the need for a deeper understanding of business actors' experiences in shaping brand identity amidst changing consumer behavior and digital marketing. This study aims to explore branding strategies in building a brand. awareness of coffee SMEs shop in Kendari City. The method used was qualitative research with a phenomenological approach through in-depth interviews, observation, and documentation of informants directly involved in branding practices. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results of the study indicate that brand Awareness is built through a consistent brand identity, a pleasant customer experience, active marketing communications, and a responsive digital presence. These findings confirm that branding in MSME coffee A shop serves not only as a promotional tool but also as a means of building emotional connection and differentiation in the local market. Consequently, MSMEs need to strengthen branding strategies that are simple, consistent, and appropriate to the local social context to maintain business competitiveness now and in the future.